Surface-modified zinc oxide particles, dispersion, cosmetic, and method for producing surface-modified zinc oxide particles

Surface modified zinc oxide particles treated with a hydrolyzed silane coupling agent improve ultraviolet shielding and transparency, addressing the limitations of existing technologies in cosmetic applications.

JP7625888B2Active Publication Date: 2025-02-04SUMITOMO OSAKA CEMENT CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021026403
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-22
Publication Date
2025-02-04
Estimated Expiration
2041-02-22

AI Technical Summary

Technical Problem

Existing surface modified zinc oxide particles do not provide sufficient ultraviolet shielding and transparency, particularly in cosmetic applications, and there is a need for improved methods to enhance their performance.

Method used

The surface modified zinc oxide particles are treated with a hydrolyzed surface treatment agent, such as a silane coupling agent with an alkoxy group, to achieve a color difference ΔE of 4.0 or less before and after pseudo-solar illumination, thereby improving ultraviolet shielding and transparency.

Benefits of technology

The treated particles exhibit enhanced ultraviolet shielding and transparency, maintaining these properties even after exposure to environmental conditions, making them suitable for use in cosmetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625888000001
    Figure 0007625888000001
  • Figure 0007625888000002
    Figure 0007625888000002
Patent Text Reader

Abstract

To provide a surface-modified zinc oxide particle excellent in ultraviolet light shield properties.SOLUTION: In a surface-modified zinc oxide particle, a particle surface of a zinc oxide particle is treated with a hydrolyzable surface preparation agent. The surface-modified zinc oxide particle has a color difference ΔE of 4.0 or less before and after pseudo-sunlight irradiation.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to surface-modified zinc oxide particles, a method for producing the same, a dispersion liquid, and a cosmetic composition. [Background technology]

[0002] Zinc oxide is known to have excellent ultraviolet shielding properties, high gas barrier properties, and high transparency. Therefore, particles made of zinc oxide (hereinafter referred to as "zinc oxide particles") are used as a material for forming various materials that have functions such as ultraviolet shielding and gas barrier, and also require transparency. Examples of such materials include ultraviolet shielding films, ultraviolet shielding glass, cosmetics, and gas barrier films.

[0003] As a method for improving the transparency of the above-mentioned various materials, for example, a method for reducing the primary particle size of zinc oxide particles, which is a forming material, is mentioned. As a method for reducing the primary particle size of zinc oxide particles, various methods such as a thermal decomposition method and a gas phase method have been considered (for example, see Patent Documents 1 and 2).

[0004] When zinc oxide particles are used in cosmetics, the surfaces of the zinc oxide particles are subjected to a surface treatment with a surface treatment agent in order to adapt the surfaces of the zinc oxide particles to the properties of the cosmetic and to suppress the catalytic activity of the zinc oxide particles. In the following description, zinc oxide particles that have been surface-treated with a surface treatment agent and have the surface treatment agent on their surfaces are referred to as surface-modified zinc oxide particles. Such surface-modified zinc oxide particles are blended directly into cosmetics, or in the form of a dispersion in which they are dispersed in a dispersion medium, and then blended into cosmetics.

[0005] When zinc oxide particles are incorporated into oil-based cosmetics or the oil phase of emulsions, the zinc oxide particles are surface-treated with a silane coupling agent having an alkoxy group (see, for example, Patent Documents 3 and 4). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2002-284527 A [Patent Document 2] JP 2000-95519 A [Patent Document 3] International Publication No. 2017 / 130632 [Patent Document 4] JP 2007-51188 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, there has been a demand for further improvement in the ultraviolet shielding properties of surface-modified zinc oxide particles.

[0008] The present invention has been made in view of the above circumstances, and aims to provide surface-modified zinc oxide particles having excellent ultraviolet shielding properties and a method for producing the same, as well as a dispersion and a cosmetic composition containing such surface-modified zinc oxide particles. [Means for solving the problem]

[0009] That is, the surface-modified zinc oxide particles of the present invention are surface-modified zinc oxide particles in which the particle surfaces of zinc oxide particles are treated with a hydrolyzable surface treatment agent, The hydrolyzable surface treatment agent is a silane coupling agent having an alkoxy group, and the silane coupling agent having an alkoxy group is represented by the following general formula (1): R 1 Si(OR 2 ) 3 ···(1) (R 1 is an alkyl group having 1 to 18 carbon atoms, a fluoroalkyl group, or a phenyl group; R 2 represents an alkyl group having 1 to 4 carbon atoms. The color difference ΔE before and after irradiation with simulated sunlight is 4.0 or less.

[0010] The dispersion of the present invention contains the above-mentioned surface-modified zinc oxide particles and a dispersion medium.

[0011] The cosmetic of the present invention contains at least one selected from the group consisting of the above-mentioned surface-modified zinc oxide particles and the above-mentioned dispersion liquid, and a cosmetic base raw material.

[0012] The method for producing surface-modified zinc oxide particles of the present invention is a method for producing the above-mentioned surface-modified zinc oxide particles, and includes a first step of mixing a surface treatment agent with water to prepare a hydrolyzed liquid, a second step of mixing the hydrolyzed liquid with zinc oxide particles to prepare a first mixture, and a step of drying the first mixture obtained in the second step. Effect of the Invention

[0013] According to the present invention, it is possible to provide surface-modified zinc oxide particles having excellent ultraviolet shielding properties. Furthermore, according to the present invention, it is possible to provide a dispersion liquid and a cosmetic preparation containing such surface-modified zinc oxide particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The surface-modified zinc oxide particles, the method for producing the same, the dispersion liquid, and the cosmetic composition according to the present invention will be described below. It should be noted that the present embodiment is specifically described to allow a better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified. The present invention allows for changes, omissions, substitutions, additions, etc. of numerical values, amounts, materials, types, times, temperatures, order, etc., within the scope of the gist of the invention.

[0015] [Surface-modified zinc oxide particles] The surface-modified zinc oxide particles of this embodiment are zinc oxide particles whose particle surfaces have been treated with a hydrolyzable surface treatment agent, and have a color difference ΔE before and after irradiation with simulated solar light of 4.0 or less. The color difference ΔE is preferably 3.5 or less, more preferably 3.0 or less, even more preferably 2.5 or less, and particularly preferably 2.0 or less. The lower limit of the color difference ΔE is 0, but it may be 0.01, 0.05, or 0.1. The surface-modified zinc oxide particles of this embodiment have a color difference ΔE of 4.0 or less, and therefore have excellent ultraviolet shielding properties.

[0016] In this embodiment, the color difference ΔE before and after irradiation with artificial solar light refers to a value measured by the following measurement method.

[0017] 3 g of t-butyl methoxydibenzoylmethane, 3 g of polyhydroxystearic acid, and 94 g of tri(caprylic / capric acid)glyceryl are mixed to prepare a solution in which t-butyl methoxydibenzoylmethane is completely dissolved. Next, 2.0 g of the obtained solution and 3.0 g of surface-modified zinc oxide particles are mixed in a kneader (manufactured by Thinky Corporation, model number: ARE-310) until homogenous to obtain a mixed solution. Next, the resulting mixture is sandwiched between an assembled quartz cell for a spectrophotometer (manufactured by GL Sciences, model number: AB20-UV-05) so that the optical path length is 0.5 mm, to prepare an assembled cell. Next, the assembled cell obtained was set in an ultraviolet-visible-near infrared spectrophotometer (manufactured by JASCO Corporation, model number: V-770), and the diffuse reflectance spectrum of the mixture was measured using an integrating sphere. From the measurement results, the L1 * , a1 * , b1 * Calculate. Next, a xenon lamp from a small light irradiation test device (manufactured by Iwasaki Electric, model number: EYE SUN-CUBE Xenon) was used to measure the cumulative light intensity of 300 kJ / m 2 The assembled cell containing the above mixed solution is irradiated with simulated solar light of 1000 nm. After irradiation, the assembled cell was set back in the UV-Vis-NIR spectrophotometer, and the diffuse reflectance spectrum was measured in the same manner as above. From the measurement results, the L2 * , a2 * , b2 * Calculate. Then, the color difference ΔE = ((L2 * -L1 * )2 +(a2 * -a1 * ) 2 +(b2 * -b1 * ) 2 ) 1 / 2 Calculate. In addition, L1 * , a1 * , b1, * L2 * , a2 * , b2 * L * a * b * This is a value on the color space chromaticity diagram.

[0018] This measurement method is a test for evaluating the surface treatment state of the surface-modified zinc oxide particles of this embodiment using simulated sunlight. The light irradiation test device uses a xenon light source that approximates sunlight. Therefore, irradiation by a xenon lamp using this measurement device can be considered to be equivalent to exposure to actual sunlight. The integrated light amount in this measurement method is 300 kJ / m 2 This simulated sunlight irradiation can evaluate the effects of ultraviolet rays equivalent to those of exposure to actual sunlight for about 10 minutes. When the color difference ΔE of the surface-modified zinc oxide particles produced in the examples was measured, the measurement results of the color difference ΔE did not change significantly between when the irradiation time was 10 minutes and when it was 3 hours. Therefore, in this measurement method, an accumulated light amount of 300 kJ / m can be considered to be equivalent to an irradiation time of sunlight of about 10 minutes. 2 It was evaluated as follows. The measurement method in this embodiment will be described. t-Butyl methoxydibenzoylmethane is an organic UV absorber commonly used in cosmetics for UV protection. Polyhydroxystearic acid is a dispersant, which is added in this measurement to uniformly mix the surface-modified zinc oxide particles and t-butyl methoxydibenzoylmethane in the solvent. Caprylic / capric triglyceride is a common solvent used in cosmetics.

[0019] When the above mixture containing surface-modified zinc oxide particles and t-butyl methoxydibenzoylmethane is exposed to simulated sunlight, if the surface treatment is insufficient, the photocatalytic activity of the zinc oxide particles and the elution of zinc ions will alter the t-butyl methoxydibenzoylmethane, causing the mixture to discolor. The present inventors have found that if zinc oxide particles are subjected to a surface treatment so that the color difference ΔE is 4.0 or less, the ultraviolet shielding ability of the surface-modified zinc oxide particles is improved, and have completed the present invention. The present inventors have also found that surface-modified zinc oxide particles having the color difference ΔE of 4.0 or less can be obtained by hydrolyzing a hydrolyzable surface modifier in advance and then performing a surface treatment.

[0020] In this embodiment, the reason why the ultraviolet shielding property of the surface-modified zinc oxide particles is improved by the color difference ΔE being 4.0 or less is unclear. The reason why the color difference ΔE is small is presumed to be due to the suppression of photocatalytic activity and elution of zinc ions. However, there is no method for directly measuring how the hydrolyzable surface modifier modifies the surface of the zinc oxide particles. Therefore, it is unclear how the surface modifier previously hydrolyzed modifies the surface of the zinc oxide particles to reduce the color difference ΔE. It is presumed that the surface modifier is uniformly and densely present on the surface of the zinc oxide particles, but this alone may not be sufficient to explain the reason. In this embodiment, the effect of using a surface treatment agent that has been hydrolyzed in advance, making the color difference ΔE 4.0 or less and improving the ultraviolet shielding property of the surface-modified zinc oxide particles, is presumably manifested by a complex intertwining of many factors. Specifically, it is presumed that this effect is manifested by a complex intertwining of many factors, such as the shape, specific surface area, and particle size distribution of the zinc oxide particles, the degree of hydrolysis of the hydrolyzable surface treatment agent, the adhesion state of the hydrolyzable surface treatment agent to the zinc oxide particles, and the adhesion rate of the hydrolyzable surface treatment agent to the zinc oxide particles. Therefore, it is considered almost impossible to directly specify the characteristics of the surface-modified zinc oxide particles of this embodiment based on the surface state of the zinc oxide particles that have been surface-modified after hydrolyzing the hydrolyzable surface treatment agent in advance.

[0021] Therefore, the inventors conducted various studies and, focusing on the above-mentioned color difference ΔE, discovered that the ultraviolet shielding property of surface-modified zinc oxide particles can be improved by surface-treating zinc oxide particles with a pre-hydrolyzed surface treatment agent so that the above-mentioned color difference ΔE is 4.0 or less.

[0022] The surface-modified zinc oxide particles of this embodiment preferably have a total light transmittance at a wavelength of 360 nm, as measured by the following measurement method, of 48% or less, more preferably 40% or less, and even more preferably 35% or less. By incorporating surface-modified zinc oxide particles having a total light transmittance at a wavelength of 360 nm, i.e., the sum of the linear transmittance and diffuse transmittance, of 48% or less, it is possible to obtain a cosmetic preparation with excellent ultraviolet shielding properties. The lower limit of the total light transmittance at a wavelength of 360 nm may be 0%, 1%, 10%, or 20%.

[0023] The surface-modified zinc oxide particles of this embodiment preferably have a linear transmittance at a wavelength of 550 nm measured by the following measurement method of 80% or more, more preferably 85% or more, and even more preferably 90% or more. By incorporating surface-modified zinc oxide particles having an in-line transmittance of 80% or more at a wavelength of 550 nm, a cosmetic preparation with excellent transparency can be obtained. The upper limit of the in-line transmittance at a wavelength of 550 nm may be 100%, 99%, or 98%.

[0024] In this embodiment, the total light transmittance at a wavelength of 360 nm and the linear transmittance at a wavelength of 550 nm are measured by the following measurement method. 10 g of surface-modified zinc oxide particles, 88 g of cyclopentasiloxane (manufactured by Dow Toray, model number: DOWSIL SH245 Fluid), and 2 g of polyglyceryl-3 polydimethylsiloxyethyl dimethicone (manufactured by Shin-Etsu Chemical Co., Ltd., model number: KF-6106) are mixed to obtain a dispersion liquid. Next, this mixture is dispersed using a homogenizer (manufactured by IKA, ULTRA-TURRAX (registered trademark) series: T25basic) at 9500 rpm for 5 minutes to obtain a dispersion for evaluation.

[0025] The obtained dispersion for evaluation is diluted with cyclopentasiloxane so that the concentration of the surface-modified zinc oxide particles becomes 0.005% by mass. The diluted solution is placed in a quartz cell with an optical path length of 10 mm, and the total light transmittance at 360 nm and the linear transmittance at 550 nm are measured using an ultraviolet-visible-near infrared spectrophotometer (manufactured by JASCO Corporation, model number: V-770).

[0026] The surface-modified zinc oxide particles of this embodiment preferably have a particle size (d90) at a cumulative volume percentage of 90% in the particle size distribution measured by the following measurement method of 1 μm or less, more preferably 0.5 μm or less, even more preferably 0.4 μm or less, and particularly preferably 0.3 μm or less. By blending surface-modified zinc oxide particles having a d90 of 1 μm or less into a cosmetic, it is possible to obtain a cosmetic having excellent transparency and ultraviolet shielding properties. The lower limit of d90 may be 0.05 μm or 0.1 μm.

[0027] The d90 of the surface-modified zinc oxide particles of this embodiment means a value measured by the following measurement method. 10 g of surface-modified zinc oxide particles, 88 g of cyclopentasiloxane (manufactured by Dow Toray, model number: DOWSIL SH245 Fluid), and 2 g of polyglyceryl-3 polydimethylsiloxyethyl dimethicone (manufactured by Shin-Etsu Chemical Co., Ltd., model number: KF-6106) are mixed to obtain a dispersion liquid. Next, this mixture is dispersed using a homogenizer (manufactured by IKA, ULTRA-TURRAX (registered trademark) series: T25basic) at 9500 rpm for 5 minutes to obtain a dispersion for evaluation.

[0028] The obtained dispersion for evaluation is diluted with cyclopentasiloxane so that the content of surface-modified zinc oxide particles becomes 0.1 mass%. Using this diluted solution, a dynamic light scattering particle size distribution measuring device (Microtrack Bell, model number: NANOTRAC WAVE) is used to measure the particle size (d90) when the cumulative volume percentage of the particle size distribution is 90%. In addition, the particle size (d10) when the cumulative volume percentage of the particle size distribution is 10% and the particle size (d50) when the cumulative volume percentage of the particle size distribution is 50% can also be measured.

[0029] The surface-modified zinc oxide particles of this embodiment preferably have a total light transmittance of 40% or less at a wavelength of 360 nm after an accelerated test in which the particles are exposed to an environment of 85° C. and 95% RH for 48 hours. By blending surface-modified zinc oxide particles having a total light transmittance of 40% or less at a wavelength of 360 nm after an accelerated test into a cosmetic, a cosmetic having excellent stability over time can be obtained. The lower limit of the total light transmittance at a wavelength of 360 nm after the accelerated test may be 0%, 1%, 10%, or 20%.

[0030] The surface-modified zinc oxide particles of this embodiment preferably have a linear transmittance of 90% or more at a wavelength of 550 nm after an accelerated test in which the particles are exposed to an environment of 85° C. and 95% RH for 48 hours. By blending surface-modified zinc oxide particles having a linear transmittance of 90% or more at a wavelength of 550 nm after an accelerated test into a cosmetic, a cosmetic having excellent stability over time can be obtained. The upper limit of the in-line transmittance at a wavelength of 550 nm after the accelerated test may be 100%, 99%, or 98%.

[0031] The surface-modified zinc oxide particles of this embodiment preferably have a d90 of 0.3 μm or less after an accelerated test in which the particles are exposed to an environment of 85° C. and 95% RH for 48 hours. By blending surface-modified zinc oxide particles having a d90 of 0.3 μm or less after an accelerated test into a cosmetic, a cosmetic having excellent stability over time can be obtained. The lower limit of d90 may be 0.05 μm or 0.1 μm.

[0032] The specific surface area of ​​the surface-modified zinc oxide particles of this embodiment can be selected arbitrarily, but is preferably 1.5 m 2 / g or more, and 2.5m 2 / g or more is more preferable, and 2 The specific surface area of ​​the surface-modified zinc oxide particles is preferably 55 m / g or more. 2 / g or less, 2 / g or less, and 2 More preferably, the specific surface area of ​​the surface-modified zinc oxide particles is 40 m 2 / g or less, 2 / g or less, 2 The specific surface area of ​​the surface-modified zinc oxide particles may be in any combination of the upper and lower limits. The specific surface area of ​​the surface-modified zinc oxide particles is 1.5 m 2 / g or more 50m 2 / g or less, the cosmetic composition will have excellent transparency and ultraviolet shielding properties when blended therewith.

[0033] To increase the transparency of a cosmetic, the specific surface area of ​​the surface-modified zinc oxide particles should be 8m 2 / g or more, and 15m 2 / g or more is more preferable, and 20m 2 It is more preferable that the molecular weight is 1 / g or more. For example, the specific surface area of ​​surface-modified zinc oxide particles is 20 m 2 / g or more and 50m 2 / g or less, and 2 / g or more and 48m 2 / g or less is more preferable, and 20m 2 / g or more and 46m 2 It is more preferable that the molecular weight is 20.0m / g or less. 2 / g or more and 30.0m 2 / g or less, 20.0m 2 / g or more and 38.0m 2 / g or less, 20.0m 2 / g or more and 44.0m 2 / g or less. When the specific surface area of ​​the surface-modified zinc oxide particles is equal to or greater than the above lower limit, a cosmetic having excellent transparency can be obtained when the surface-modified zinc oxide particles are blended into a cosmetic. On the other hand, when the specific surface area of ​​the surface-modified zinc oxide particles is equal to or less than the above upper limit, the surface energy of the particles is not too large, and the particles can be blended into a cosmetic with less energy.

[0034] On the other hand, if you want to increase the UVA region ultraviolet ray shielding ability when blended into cosmetics, the specific surface area of ​​the surface-modified zinc oxide particles should be 20 m 2 / g, and preferably less than 15m 2 / g or less is more preferable, and 2 It is more preferable that the molecular weight is not more than 1 / g. For example, the specific surface area of ​​surface-modified zinc oxide particles is 1.5 m 2 / g or more 20m 2 / g, and preferably less than 1.5m 2 / g or more 15m 2 / g or less is more preferable, and 1.5m 2 / g or more 8m 2 / g or less is even more preferable. When the specific surface area of ​​the surface-modified zinc oxide particles is equal to or greater than the above lower limit, a cosmetic having transparency can be obtained when the surface-modified zinc oxide particles are blended into a cosmetic. On the other hand, when the specific surface area of ​​the surface-modified zinc oxide particles is less than the above upper limit, the surface energy of the particles is not too large, so that the particles can be blended into a cosmetic with less energy, and a cosmetic having excellent ultraviolet ray shielding properties in the UVA region can be obtained.

[0035] The specific surface area (unit: m 2 / g) refers to the BET specific surface area determined by the BET method. The specific surface area of ​​the surface-modified zinc oxide particles can be measured, for example, by the BET method using a fully automatic specific surface area measuring device (product name: Macsorb HM Model-1201, manufactured by Mountec Co., Ltd.).

[0036] In this embodiment, "treated with a surface treatment agent" means that the surface treatment agent contacts or bonds with the zinc oxide particles due to an interaction between them. Examples of the contact include physical adsorption. Examples of the bond include ionic bonds, hydrogen bonds, covalent bonds, etc.

[0037] The amount of the surface treatment agent in the surface-modified zinc oxide particles may be appropriately adjusted according to the specific surface area of ​​the zinc oxide particles and the hydrophobicity of the cosmetic to be blended. For example, the amount of the surface treatment agent in the surface-modified zinc oxide particles is preferably 1% by mass or more and 20% by mass or less, more preferably 5% by mass or more and 18% by mass or less, and even more preferably 8% by mass or more and 16% by mass or less, based on the total mass of the zinc oxide particles and the surface treatment agent. By the amount of the surface treatment agent being equal to or more than the lower limit, the hydrophilic zinc oxide particles can be blended into an oil-based cosmetic. In addition, by the amount of the surface treatment agent being equal to or less than the upper limit, the ultraviolet shielding property of the zinc oxide particles when blended into the cosmetic is fully exhibited.

[0038] From the viewpoint of reducing the color difference ΔE and improving the stability over time, the content of the surface treatment agent is preferably from 4 mass% to 20 mass% inclusive, more preferably from 6 mass% to 18 mass% inclusive, and even more preferably from 8 mass% to 16 mass% inclusive, based on the total mass of the zinc oxide particles and the surface treatment agent.

[0039] When the surface treatment agent is a silane coupling agent, the content of the surface treatment agent in the surface-modified zinc oxide particles can be calculated, for example, by quantitatively analyzing the amount of Si in the surface-modified zinc oxide particles using an inductively coupled plasma optical emission spectrometer.

[0040] "Zinc oxide particles" The specific surface area of ​​the zinc oxide particles (before surface treatment) in this embodiment can be selected arbitrarily, but is preferably 1.5 m 2 / g or more, and 2.5m 2 / g or more is more preferable, and 2 It is more preferable that the specific surface area of ​​the zinc oxide particles is 50 m 2 / g or less, and 2 / g or less. If necessary, the specific surface area of ​​the zinc oxide particles is 40 m 2 / g or less, 2 / g or less, 2 / g or less. The specific surface area of ​​zinc oxide particles before surface treatment and the specific surface area of ​​surface-modified zinc oxide particles vary somewhat depending on how the silane coupling agent is attached, but do not change significantly. Therefore, in order to obtain surface-modified zinc oxide particles with a desired specific surface area, zinc oxide particles having the desired specific surface area may be used. That is, the surface-modified zinc oxide particles of the present embodiment can preferably have a specific surface area that is similar to the preferred specific surface area values ​​and ranges of the zinc oxide particles described above.

[0041] L of zinc oxide particles before treatment * a * b *b in the color space chromaticity diagram * is preferably 10 or less. * When the above range is used, the b * The b of the surface-modified zinc oxide particles can be 4.0 or more and 18 or less. * However, the b of zinc oxide particles before surface treatment * As a result, the yellowness can be suppressed to a level suitable for use in cosmetics. * The lower limit of is not particularly limited, and may be 0, 1.0, or 1.5.

[0042] "Hydrolyzable surface treatment agent" The hydrolyzable surface treatment agent of the present embodiment is not particularly limited as long as it is hydrolyzable and can be used in cosmetics. In the present embodiment, "hydrolyzable" includes not only hydrolysis of alkoxy groups, but also dealkalization of metal soaps and dehydrogenation of SiH of silicone.

[0043] Examples of such surface treatment agents include at least one selected from the group consisting of silane compounds, silicone compounds, fatty acids, fatty acid soaps, fatty acid esters, and organic titanate compounds. A surfactant may also be used.

[0044] Examples of the silane compound used in the surface treatment include alkylsilanes and fluoroalkylsilanes. Examples of alkylsilanes include methyltrimethoxysilane, ethyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, and octyltriethoxysilane. Examples of the fluoroalkylsilane include trifluoromethylethyltrimethoxysilane and heptadecafluorodecyltrimethoxysilane. Among these silane compounds, alkylsilanes are preferred, and octyltriethoxysilane is particularly preferred. These silane compounds may be used alone or in combination of two or more.

[0045] Examples of silicone compounds include silicone oil, methicone, dimethicone, hydrogen dimethicone, triethoxysilylethyl polydimethylsiloxyethyl dimethicone, triethoxysilylethyl polydimethylsiloxyethylhexyl dimethicone, (acrylates / tridecyl acrylate / triethoxysilylpropyl methacrylate / dimethicone methacrylate) copolymer, and triethoxycaprylylsilane. Examples of silicone oils include methylhydrogenpolysiloxane, dimethylpolysiloxane, and methylphenylpolysiloxane. These silicone compounds may be used alone or in combination of two or more thereof. Furthermore, the silicone compound may be a copolymer of these silicone compounds.

[0046] Examples of fatty acids include palmitic acid, isostearic acid, stearic acid, lauric acid, myristic acid, behenic acid, oleic acid, rosin acid, and 12-hydroxystearic acid. Examples of fatty acid soaps include magnesium stearate, zinc stearate, aluminum stearate, calcium stearate, magnesium myristate, zinc myristate, aluminum distearate, aluminum dimyristate, and aluminum 12-hydroxystearate. Examples of fatty acid esters include dextrin fatty acid esters, cholesterol fatty acid esters, sucrose fatty acid esters, and starch fatty acid esters.

[0047] Examples of organic titanate compounds include isopropyl triisostearoyl titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl tri(dodecyl)benzenesulfonyl titanate, neopentyl(diallyl)oxy-tri(dioctyl)phosphate titanate, and neopentyl(diallyl)oxy-trineododecanoyl titanate.

[0048] Of the above surface treatment agents, it is preferable to use a silane coupling agent having an alkoxy group.

[0049] "Silane coupling agent having an alkoxy group" The silane coupling agent having an alkoxy group can be arbitrarily selected, and preferred examples include silane coupling agents represented by the following general formula (1) that can be used in cosmetics. R 1 Si(OR 2 )3···(1) (R 1 is an alkyl group having 1 to 18 carbon atoms, a fluoroalkyl group, or a phenyl group; R 2 represents an alkyl group having 1 to 4 carbon atoms.

[0050] Such a silane coupling agent is preferably at least one selected from the group consisting of alkylalkoxysilanes, allylalkoxysilanes, polysiloxanes having an alkyl group on the side chain, and polysiloxanes having an allyl group on the side chain.

[0051] Examples of alkylalkoxysilanes include methyltrimethoxysilane, methyltriethoxysilane, methyltrippropoxysilane, methyltributoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltrippropoxysilane, ethyltributoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-propyltrippropoxysilane, n-propyltributoxysilane, isopropyltrimethoxysilane, isopropyltriethoxysilane, isopropyltrippropoxysilane, isopropyltributoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenyltrippropoxysilane, phenyltributoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane (triethoxycaprylylsilane), and n-octadecyltrimethoxysilane.

[0052] As the silane coupling agent, for example, a polymer-type silane coupling agent having a siloxane skeleton as the main chain and an alkoxy group and an acrylic group within the molecular structure, such as dimethoxydiphenylsilane-triethoxycaprylylsilane crosspolymer, triethoxysilylethyl polydimethylsiloxyethyl dimethicone, or triethoxysilylethyl polydimethylsiloxyethylhexyl dimethicone, can be used.

[0053] As the silane coupling agent, for example, fluoroalkylalkoxysilanes such as trifluoropropyltrimethoxysilane, perfluorooctyltriethoxysilane, and tridecafluorooctyltriethoxysilane can be used.

[0054] These silane coupling agents may be used alone or in combination of two or more.

[0055] Among the above silane coupling agents, the silane coupling agent having an octyl group in the molecule is more preferred.Specifically, the silane coupling agent that can be applied to a wide range of polar oil phases from natural oil, ester oil to silicone oil is more preferred.As such a silane coupling agent, at least one selected from the group consisting of n-octyltriethoxysilane, n-octyltrimethoxysilane and dimethoxydiphenylsilane-triethoxycaprylylsilane crosspolymer is particularly preferred. These silane coupling agents may be used alone or in combination of two or more.

[0056] In the surface-modified zinc oxide particles of this embodiment, in addition to a silane coupling agent, the zinc oxide particles may be surface-treated using a surface treatment agent other than a silane coupling agent that is used in cosmetics, as long as the properties of the surface-modified zinc oxide particles are not impaired.

[0057] According to the surface-modified zinc oxide particles of this embodiment, the particle surface of the zinc oxide particles is treated with a hydrolyzable surface treatment agent, and the color difference ΔE before and after irradiation with simulated solar light is 4.0 or less, and therefore the particles have excellent ultraviolet shielding properties.

[0058] "Method for producing surface-modified zinc oxide particles" The method for producing surface-modified zinc oxide particles of this embodiment is a method for producing the above-mentioned surface-modified zinc oxide particles, and includes a first step of mixing a surface treatment agent with water to prepare a hydrolyzed liquid, a second step of mixing the hydrolyzed liquid with zinc oxide particles to prepare a first mixture, and a step of drying the first mixture obtained in the second step.

[0059] Furthermore, the method for producing surface-modified zinc oxide particles of this embodiment may include, after the second step, a third step of adding and mixing the hydrolyzed liquid obtained in the first step to the first mixture obtained in the second step to prepare a second mixture containing the first mixture and the hydrolyzed liquid, and drying the second mixture obtained in the third step.

[0060] The surface treatment of this embodiment may be carried out by a dry method or a wet method.

[0061] A method for performing a dry surface treatment will now be described. "First step of preparing hydrolyzed liquid" In this step, the surface treatment agent is mixed with water to prepare a hydrolyzed liquid. By using the hydrolyzed liquid in which at least a part of the surface treatment agent has been hydrolyzed in advance, it is possible to produce surface-modified zinc oxide particles having a small color difference ΔE. It is common to hydrolyze a surface treatment agent in advance, but the significantly smaller color difference ΔE of the surface-modified zinc oxide particles surface-treated with a hydrolyzed surface treatment agent is a remarkable effect beyond the range of prediction by a person skilled in the art.

[0062] The hydrolysis liquid may be prepared by maintaining a mixture of the surface treatment agent and water at a constant temperature for a predetermined period of time, which can further promote the hydrolysis of the surface treatment agent. In this treatment, the temperature of the mixed liquid is not particularly limited and can be appropriately changed depending on the type of surface treatment agent, but is preferably, for example, from 5°C to 65°C, and more preferably from 30°C to 60°C.

[0063] The retention time is not particularly limited, but is preferably from 10 minutes to 180 minutes, and more preferably from 30 minutes to 120 minutes. During retention of the mixture, the mixture may be appropriately stirred.

[0064] The surface treatment agent used in the first step may be the same as that described above, and therefore a description thereof will be omitted. The water is not particularly limited as long as it is water that is generally used in cosmetics, and pure water, ion-exchanged water, distilled water, purified water, ultrapure water, natural water, etc. can be used.

[0065] In this step, in order to control the hydrolysis reaction of the surface treatment agent, it is preferable to mix a solvent other than water. The solvent is not particularly limited as long as it does not excessively control the hydrolysis of the surface treatment agent, and for example, an alcohol-based solvent can be mixed.

[0066] Examples of the alcohol-based solvent include branched or linear alcohol compounds having 1 to 4 carbon atoms, which can be used alone or in combination of two or more. The alcohol compound contained in the alcohol-based solvent may be any of primary, secondary, and tertiary alcohols. The alcohol compound contained in the alcohol-based solvent may be any of monohydric, dihydric, and trihydric alcohols. More specifically, examples of the alcohol-based solvent include methanol, ethanol, 1-propanol, isopropyl alcohol, 1-butyl alcohol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, methanediol, 1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-butene-1,4-diol, 1,4-butynediol, glycerin, diethylene glycol, and 3-methoxy-1,2-propanediol. Among these alcohol-based solvents, ethanol and isopropyl alcohol are preferred from the viewpoints that the hydrolysis reaction can be easily controlled and that they have little effect when mixed into cosmetics.

[0067] In this step, a catalyst may be mixed in order to promote the hydrolysis reaction of the surface treatment agent. The catalyst may be an acid or a base. The acid catalyzes the hydrolysis reaction of the surface treatment agent in the dispersion, while the base catalyzes the condensation reaction of the hydrolyzed surface treatment agent with the silanol groups on the particle surface.

[0068] Examples of the acid include inorganic acids such as hydrochloric acid, hydrobromic acid, hydroiodic acid, sulfuric acid, nitric acid, boric acid, phosphoric acid, etc., and organic acids such as acetic acid, citric acid, formic acid, etc. These acids may be used alone or in combination of two or more. Examples of the base include sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, ammonia, amines, etc. These bases may be used alone or in combination of two or more.

[0069] The content of the surface treatment agent in the mixed liquid is not particularly limited, but is preferably from 20% by mass to 70% by mass, and more preferably from 30% by mass to 60% by mass, for example.

[0070] The water content in the mixed liquid is not particularly limited, but is preferably, for example, from 1% by mass to 20% by mass, more preferably from 3% by mass to 15% by mass, and even more preferably from 5% by mass to 10% by mass.

[0071] The content of the solvent in the mixed liquid is not particularly limited, but is preferably 20% by mass or more and 70% by mass or less, and more preferably 30% by mass or more and 60% by mass or less. This allows the content of the surface treatment agent in the hydrolysis liquid to be sufficiently large, and allows a sufficient amount of water to be contained in the mixed liquid. As a result, the hydrolysis reaction of the surface treatment agent can be efficiently promoted.

[0072] The content of the catalyst in the mixed liquid is not particularly limited, and is, for example, preferably from 10 ppm to 1000 ppm, and more preferably from 20 ppm to 800 ppm, which can sufficiently promote the hydrolysis reaction of the surface treatment agent.

[0073] "Second step of preparing a first mixture" This step is a step of mixing the above hydrolysis liquid with zinc oxide particles to prepare a mixture, and then performing a surface treatment on the zinc oxide particles with a surface treatment agent in a dry manner. The zinc oxide particles may be the same as those described above, and therefore a detailed description thereof will be omitted.

[0074] The method of mixing the hydrolyzed liquid with the zinc oxide particles is not particularly limited, as long as the mixing is performed with a stirring strength sufficient to attach the surface treatment agent to the surface of the zinc oxide particles. For example, the zinc oxide particles and the hydrolyzed liquid are put into a mixer such as a Henschel mixer or a super mixer, and stirred strongly at high speed for a certain period of time. From the viewpoint of promoting the surface treatment reaction, it is preferable to heat the mixture at a temperature of 70°C to 200°C while continuing to stir.

[0075] The mixing ratio of the hydrolysis liquid and zinc oxide particles is not particularly limited, but it is preferable to mix the surface treatment agent so that the surface treatment agent accounts for 1% by mass or more and 20% by mass or less of the total mass of the zinc oxide particles and the surface treatment agent, including the third step described below. The mixing ratio is more preferably 5% by mass or more and 18% by mass or less, and even more preferably 8% by mass or more and 16% by mass or less.

[0076] "Third step of preparing a second mixture" After the second step, this step may or may not be carried out. The mixture obtained in the second step may be dried at 60° C. to 100° C. to remove moisture before carrying out this step. In this step, the first mixture obtained in the second step is mixed with the hydrolyzed liquid to obtain a mixture, thereby performing surface treatment on the zinc oxide particles with a surface treatment agent. By carrying out the surface treatment twice, the surface treatment agent can be more easily attached uniformly to the particle surfaces. The surface treatment step may be carried out three, four or more times.

[0077] The mixing method may be the same as in the second step, in which the mixing is performed with a stirring intensity sufficient to cause the surface treatment agent to adhere to the surfaces of the zinc oxide particles. As in the second step, the mixture may be heated at a temperature of 70° C. to 200° C. while continuing to stir.

[0078] The mixing ratio of the hydrolysis liquid and zinc oxide particles is not particularly limited, but it is preferable to mix the surface treatment agent in the total mass of the zinc oxide particles and the surface treatment agent, including the second step, so that the surface treatment agent accounts for 1% by mass or more and 20% by mass or less. The mixing ratio is more preferably 5% by mass or more and 18% by mass or less, and even more preferably 8% by mass or more and 16% by mass or less. The mass ratio of the surface treatment agent mixed in the second step to the surface treatment agent mixed in the third step is not particularly limited, but is preferably 0.5:1 to 3:1. Since the second and subsequent surface treatment steps are carried out to suppress the remaining hydrolyzable reactive groups, it is preferable to mix a small amount of the surface treatment agent and promote the surface treatment by heating or the like.

[0079] "Drying process" This step is carried out in order to remove water and solvent remaining in the first mixture or the second mixture. In this step, the first mixture or the second mixture may be heated in a drying device until water and the solvent are removed. The drying device is not particularly limited, and examples thereof include a box dryer, a vacuum dryer, a vibration dryer, a fluidized bed dryer, a band dryer, an evaporator, a Nauta mixer, a Henschel mixer, a Ribocone, a paddle dryer, a spray dryer, a slurry dryer, a flash dryer, and a rotary dryer. The drying temperature and drying time are not particularly limited, but may be, for example, at 60° C. to 130° C. for 10 minutes to 24 hours.

[0080] "Crushing process" This step may be carried out before or after the drying step. By carrying out this step, it is possible to loosen the aggregation of the surface-modified zinc oxide particles and suppress the rough feeling when the surface-modified zinc oxide particles are incorporated into a cosmetic preparation. In other words, it is possible to improve the feeling of use when the surface-modified zinc oxide particles are used in a cosmetic preparation. The crushing step can be carried out using a crusher. The crusher can be arbitrarily selected, and examples thereof include an atomizer, a hammer mill, a jet mill, an impeller mill, and a pin mill.

[0081] By the above steps, the surface-modified zinc oxide particles of this embodiment can be produced by a dry process.

[0082] Next, a method for producing the surface-modified zinc oxide particles of this embodiment by wet treatment will be described. In the present embodiment, the term "wet treatment" refers to carrying out the surface treatment in a state in which the solvent, including that contained in the hydrolyzed liquid, is present in a total amount of 40 mass % or more in the mixture.

[0083] "First step of preparing hydrolyzed liquid" This step is the same as the dry treatment described above, so a description thereof will be omitted.

[0084] "Preparing a first mixture" This step is a step of performing a surface treatment of the zinc oxide particles with a surface treatment agent in a wet manner by mixing the hydrolyzed liquid, zinc oxide particles, and a solvent to prepare a first mixture. The mixing is preferably carried out using a disperser from the viewpoint of uniformly applying the surface treatment agent to the surfaces of the zinc oxide particles, and therefore, mixing using a disperser will be described in detail below. The zinc oxide particles can be the same as those described above, and therefore a detailed description thereof will be omitted.

[0085] In this step, the hydrolysis liquid, the solvent, and the zinc oxide particles are put into a disperser to prepare a mixed liquid. These materials may be put in simultaneously or sequentially. The order in which these materials are put in is not particularly limited. After being put into the disperser, they may be left as they are without stirring, but may be simply stirred. Also, these materials may be mixed in advance before being put into the disperser.

[0086] "solvent" The solvent is not particularly limited as long as it is a solvent that can be mixed with the surface treatment agent. Examples of the solvent include alcohols such as methanol, ethanol, n-propanol, isopropanol, and n-butanol, esters such as ethyl acetate and butyl acetate, and n-hexane, toluene, and xylene. Among these solvents, alcohols are preferred because they can be mixed with water, and among alcohols, ethanol is particularly preferred.

[0087] The content of the solvent in the mixed solution can be selected arbitrarily, but is preferably 40% by mass or more in order to suppress aggregation of zinc oxide particles. The upper limit of the content of the solvent is not particularly limited, but is preferably 95% by mass or less in terms of production efficiency.

[0088] The content of zinc oxide particles in the mixed solution can be selected arbitrarily, but from the viewpoint of both suppressing aggregation of zinc oxide particles and production efficiency, it is preferably 1% by mass or more and 55% by mass or less, and more preferably 10% by mass or more and 50% by mass or less. The content may be 15% by mass or more and 45% by mass or less, 20% by mass or more and 40% by mass or less, or 25% by mass or more and 35% by mass or less, etc.

[0089] The mixing ratio of the hydrolysis liquid and zinc oxide particles is not particularly limited, but it is preferable to mix the surface treatment agent so that the surface treatment agent accounts for 1% by mass or more and 20% by mass or less of the total mass of the zinc oxide particles and the surface treatment agent, including the third step described below. The mixing ratio is more preferably 5% by mass or more and 18% by mass or less, and even more preferably 8% by mass or more and 16% by mass or less.

[0090] "Dispersion machine" The dispersing machine is not particularly limited as long as it can impart to the mixed liquid a dispersion energy sufficient to perform surface treatment while loosening the agglomerations of zinc oxide particles. Examples of such a dispersing machine include a colloid mill, a roll mill, an ultrasonic dispersing machine, a high-pressure homogenizer, an ultimaizer, a rotary mill, a planetary mill, a bead mill, a sand mill, etc. Examples of the dispersing medium used in a dispersing device that requires a dispersing medium include granular materials having a predetermined hardness, such as zirconia, glass, alumina, titania, and silicon nitride.

[0091] In this step, the above-mentioned mixture is dispersed using a dispersing machine with a predetermined amount of energy or more to obtain surface-modified zinc oxide particles. The energy given to the mixture may be adjusted appropriately according to the size of the dispersing machine. Therefore, the dispersion conditions may be selected appropriately. For example, when dispersing with a mill, specifically, a bead mill using a container with a capacity of about 1 L, it is preferable to perform the dispersion treatment at a rotation speed of 500 rpm or more for a time period of 1 hour or more and 10 hours or less. However, the conditions may be selected as necessary, and are not limited to the above conditions. Furthermore, when dispersion treatment is performed using a mill, specifically a bead mill using a container with a capacity of about 1 L, the dispersion energy imparted to the mixture is preferably, for example, 100 W·h / kg or more and 600 W·h / kg or less, however, the conditions can be selected as necessary and are not limited to only the above conditions. In addition, because the crushing force of the bead mill depends on the centrifugal force of the beads on the outer periphery of the disk or pin in the mill, the product (impulse) of the centrifugal force and the dispersion time when the bead weight is the total weight of the beads in the mill is 0.5×10 6 N s or more and 100×10 6 It is preferable to carry out dispersion processing so that the particle size is N·s or less. In addition, the surface-modified zinc oxide particles *The dispersion treatment may be continued until the b value is 4.0 or more and 18 or less. In this case, a small amount of zinc oxide particles during the dispersion treatment is taken out and the b value of the zinc oxide particles is measured using a spectrophotometer. * The progress of the dispersion process may be confirmed by measuring the

[0092] The temperature during the step of dispersing with a dispersing machine is not particularly limited, but is preferably, for example, 20° C. or higher and 45° C. or lower.

[0093] "Third step of preparing a second mixture" After the second step, this step may or may not be carried out. In this step, the first mixture obtained in the second step is mixed with the hydrolyzed liquid to obtain a second mixture, thereby performing surface treatment on the zinc oxide particles with a surface treatment agent. By carrying out the surface treatment twice, the surface treatment agent can be more easily attached uniformly to the particle surfaces. The surface treatment step may be carried out three, four or more times.

[0094] The mixing ratio of the hydrolysis liquid and zinc oxide particles is not particularly limited, but it is preferable to mix the surface treatment agent in the total mass of the zinc oxide particles and the surface treatment agent, including the second step, so that the surface treatment agent accounts for 1% by mass or more and 20% by mass or less. The mixing ratio is more preferably 5% by mass or more and 18% by mass or less, and even more preferably 8% by mass or more and 16% by mass or less. The mass ratio of the surface treatment agent mixed in the second step to the surface treatment agent mixed in the third step is not particularly limited, but is preferably 0.5:1 to 3:1. Since the second and subsequent surface treatment steps are carried out to suppress the remaining hydrolyzable reactive groups, it is preferable to mix a small amount of the surface treatment agent and promote the surface treatment by heating or the like.

[0095] Since this step is carried out in order to suppress the remaining hydrolyzable reactive groups, it is preferable to mix while heating. That is, in the case of wet surface treatment, the surface treatment agent is uniformly adhered to the surfaces of the zinc oxide particles in the second step, and the surface treatment is further promoted in the third step. The heating temperature is not particularly limited as long as it is a temperature at which the surface treatment is promoted, and is preferably, for example, 40° C. or more and 150° C. or less. If necessary, the heating temperature may be 40° C. or more and 80° C. or less, or 60° C. to 100° C., etc.

[0096] "Drying process" This step is carried out to remove water and solvent remaining in the second mixture. In this step, it is preferable to dry using a drying device. In addition, a treatment to shorten the drying time, such as solid-liquid separation, may be performed before drying. The drying device is not particularly limited, and examples thereof include a box dryer, a vacuum dryer, a vibration dryer, a fluidized bed dryer, a band dryer, an evaporator, a Nauta mixer, a Henschel mixer, a Ribocone, a paddle dryer, a spray dryer, a slurry dryer, a flash dryer, and a rotary dryer. The drying temperature is not particularly limited as long as it is a temperature at which the solvent can be removed, and is preferably, for example, 50° C. or higher and 200° C. or lower. It may be 60° C. or higher and 150° C. or lower, or 70° C. or higher and 120° C. or lower, etc.

[0097] "Crushing process" The surface-modified zinc oxide particles after drying may be subjected to a crushing treatment using a crusher. The crusher may be selected arbitrarily, and examples thereof include an atomizer, a hammer mill, a jet mill, an impeller mill, and a pin mill. The crushing step can suppress the rough feeling of the surface-modified zinc oxide particles when blended in a cosmetic preparation, for example. In other words, the feeling of use when the surface-modified zinc oxide particles are used in a cosmetic preparation can be improved.

[0098] By the above steps, the surface-modified zinc oxide particles of this embodiment can be produced by a wet method.

[0099] [Dispersion] The dispersion liquid of the present embodiment contains the surface-modified zinc oxide particles of the present embodiment and a dispersion medium. The surface-modified zinc oxide particles of the present embodiment may be prepared and mixed with the dispersion medium to form the dispersion liquid. The dispersion liquid of the present embodiment may preferably contain a paste-like dispersion having a high viscosity.

[0100] The dispersion medium is not particularly limited as long as it can disperse the surface-modified zinc oxide particles. When the surface-modified zinc oxide particles are used for cosmetic purposes, the dispersion medium is not particularly limited as long as it can be formulated into the cosmetic. Examples of the dispersion medium include linear polysiloxanes such as dimethylpolysiloxane, methylphenylpolysiloxane, and diphenylpolysiloxane, cyclic polysiloxanes such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecamethylcyclohexasiloxane, modified polysiloxanes such as amino-modified polysiloxanes, polyether-modified polysiloxanes, alkyl-modified polysiloxanes, and fluorine-modified polysiloxanes, liquid paraffin, squalane, isoparaffin, branched light paraffin, Vaseline, ceresin, dodecane, and isododecane. Examples of hydrophobic dispersion media include hydrocarbon oils such as decane, tridecane, tetradecane, hexadecane, isohexadecane, and octadecane; ester oils such as isopropyl myristate, cetyl isooctanoate, glyceryl trioctanoate, tri(caprylic acid / capric acid)glyceryl, and alkyl benzoate (C12-15); higher fatty acids such as lauric acid, myristic acid, palmitic acid, and stearic acid; and higher alcohols such as lauryl alcohol, cetyl alcohol, stearyl alcohol, octyldodecanol, and isostearyl alcohol.Further, alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, octanol, and glycerin; esters such as ethyl acetate, butyl acetate, ethyl lactate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and γ-butyrolactone; esters such as diethyl ether, ethylene glycol monomethyl ether (methyl cellosolve), ethylene glycol monoethyl ether (ethyl cellosolve), ethylene glycol monobutyl ether (butyl cellosolve), diethylene glycol monomethyl ether, and diethylene glycol monoethyl ether. aromatic hydrocarbons such as benzene, toluene, ethylbenzene, 1-phenylpropane, isopropylbenzene, n-butylbenzene, tert-butylbenzene, sec-butylbenzene, o-, m- or p-xylene, 2-, 3- or 4-ethyltoluene; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone; amides such as dimethylformamide, N,N-dimethylacetoacetamide, N-methylpyrrolidone; nitriles such as acetonitrile; and natural oils such as oleic acid, jojoba oil, olive oil, coconut oil, grapeseed oil, castor oil, rice bran oil, horse oil, and mink oil. These dispersion media may be used alone or in combination of two or more.

[0101] When the surface-modified zinc oxide particles are used for cosmetic applications, the dispersion medium preferably used is the above-mentioned chain polysiloxane, the above-mentioned cyclic polysiloxane, the above-mentioned modified polysiloxane, the above-mentioned hydrocarbon oil, the above-mentioned ester oil, the above-mentioned higher fatty acid, the above-mentioned higher alcohol, the above-mentioned natural oil, ethanol, glycerin, or the like. These dispersion media may be used alone or in combination of two or more.

[0102] The dispersion of the present embodiment may contain commonly used additives to the extent that the properties of the dispersion are not impaired.

[0103] Examples of the additives include preservatives, dispersants, dispersion aids, stabilizers, water-soluble binders, thickeners, oil-soluble drugs, oil-soluble dyes, oil-soluble proteins, UV absorbers, and the like.

[0104] The particle size (d50) at a cumulative volume percentage of 50% in the particle size distribution of the dispersion of this embodiment may be selected arbitrarily, but is preferably 300 nm or less (0.3 μm or less), more preferably 250 nm or less, and even more preferably 200 nm or less. The upper limit of d50 may be 150 nm or less, or 100 nm or less.

[0105] The lower limit of d50 is not particularly limited, and may be, for example, 20 nm or more, 40 nm or more, or 60 nm or more. The upper and lower limits of d50 can be combined in any manner.

[0106] Furthermore, the particle size (d90) when the cumulative volume percentage of the particle size distribution in the dispersion of this embodiment is 90% is preferably 350 nm or less, more preferably 300 nm or less, and even more preferably 250 nm or less.

[0107] The lower limit of d90 is not particularly limited, and may be, for example, 60 nm or more, 80 nm or more, or 100 nm or more. The upper and lower limits of d90 can be combined in any manner.

[0108] When the d50 of the dispersion is 300 nm or less, the surface-modified zinc oxide particles are easily distributed uniformly when a cosmetic prepared using the dispersion is applied to the skin, and the ultraviolet shielding effect is improved, which is preferable. Also, when the d90 of the dispersion is 350 nm or less, the transparency of the dispersion is high, and the transparency of the cosmetic prepared using the dispersion is also high, which is preferable.

[0109] That is, by having the d50 and d90 in the dispersion of the present embodiment within the above ranges, a dispersion having excellent transparency and excellent UV shielding properties can be obtained. Furthermore, a cosmetic product prepared using this dispersion also has excellent transparency and UV shielding properties.

[0110] The cumulative volume percentage of the particle size distribution in the dispersion liquid of this embodiment can be measured, for example, by a method using a dynamic light scattering particle size distribution measuring device (manufactured by Microtrack Bell, model number: NANOTRAC WAVE).

[0111] The content of the surface-modified zinc oxide particles in the dispersion of this embodiment is appropriately adjusted according to the desired properties of the dispersion.

[0112] When the dispersion of the present embodiment is used in a cosmetic preparation, the content of the surface-modified zinc oxide particles in the dispersion is preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more. The content of the surface-modified zinc oxide particles in the dispersion is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less. The upper and lower limits for the content of the surface-modified zinc oxide particles in the dispersion can be combined in any desired manner.

[0113] By setting the content of the surface-modified zinc oxide particles in the dispersion liquid within the above range, the surface-modified zinc oxide particles are contained in the dispersion liquid at a high concentration, which improves the degree of freedom in the formulation of cosmetics prepared using the dispersion liquid, and also makes it possible to adjust the viscosity of the dispersion liquid to a range that is easy to handle.

[0114] The method for producing the dispersion of the present embodiment is not particularly limited, and may be, for example, a method in which the surface-modified zinc oxide particles of the present embodiment and a dispersion medium are mechanically dispersed using a known dispersion device.

[0115] The dispersing device can be selected as necessary, and examples of the dispersing device include a stirrer, a planetary mixer, a homomixer, an ultrasonic homogenizer, a sand mill, a ball mill, and a roll mill.

[0116] The dispersion of the present embodiment can be used in cosmetics as well as paints having ultraviolet shielding properties, gas permeation inhibiting properties, and the like.

[0117] The dispersion liquid of the present embodiment contains the surface-modified zinc oxide particles of the present embodiment, and therefore has excellent ultraviolet shielding properties.

[0118] [Composition] The composition of the present embodiment contains the surface-modified zinc oxide particles of the present embodiment, a resin, and a dispersion medium. The surface-modified zinc oxide particles of the present embodiment may be prepared and mixed with the resin and the dispersion medium to prepare the composition.

[0119] The content of the surface-modified zinc oxide particles in the composition of the present embodiment is appropriately adjusted according to the properties of the intended composition. The content of the surface-modified zinc oxide particles in the composition of the present embodiment is, for example, preferably 10% by mass or more and 40% by mass or less, more preferably 20% by mass or more and 30% by mass or less.

[0120] By setting the content of the surface-modified zinc oxide particles in the composition within the above range, the surface-modified zinc oxide particles are contained in the composition at a high concentration, and therefore the properties of the surface-modified zinc oxide particles can be fully obtained, and a composition in which the surface-modified zinc oxide particles are uniformly dispersed can be obtained.

[0121] The dispersion medium is not particularly limited as long as it is one that is generally used in industrial applications, and examples of the dispersion medium include alcohols such as methanol, ethanol, and propanol, methyl acetate, ethyl acetate, toluene, methyl ethyl ketone, and methyl isobutyl ketone.

[0122] The content of the dispersion medium in the composition of the present embodiment is not particularly limited and is appropriately adjusted depending on the intended properties of the composition.

[0123] The resin is not particularly limited as long as it is one that is generally used in industrial applications, and examples of the resin include acrylic resin, epoxy resin, urethane resin, polyester resin, and silicone resin.

[0124] The content of the resin in the composition of the present embodiment is not particularly limited and is appropriately adjusted according to the intended properties of the composition.

[0125] The composition of the present embodiment may contain commonly used additives to the extent that the properties of the composition are not impaired. Examples of the additives include a polymerization initiator, a dispersant, and a preservative.

[0126] The method for producing the composition of the present embodiment is not particularly limited. For example, the surface-modified zinc oxide particles of the present embodiment, a resin, and a dispersion medium are mechanically mixed with a known mixer.

[0127] In addition, there is also a method in which the above-mentioned dispersion liquid and a resin are mechanically mixed using a known mixer.

[0128] Examples of the mixing device include a stirrer, a planetary mixer, a homomixer, and an ultrasonic homogenizer.

[0129] A coating film can be formed by applying the composition of the present embodiment to a plastic substrate such as a polyester film by a common coating method such as roll coating, flow coating, spray coating, screen printing, brush coating, dipping, etc. These coating films can be used as ultraviolet shielding films or gas barrier films.

[0130] The composition of the present embodiment has excellent ultraviolet shielding properties because it contains the surface-modified zinc oxide particles of the present embodiment.

[0131] [Cosmetics] The cosmetic material of the present embodiment contains at least one of the surface-modified zinc oxide particles of the present embodiment and the dispersion liquid of the present embodiment, and a cosmetic base raw material.

[0132] Here, the cosmetic base raw materials refer to the raw materials that form the main body of the cosmetic product, and examples of such raw materials include oil-based raw materials, water-based raw materials, surfactants, and powder raw materials. Examples of oil-based raw materials include fats and oils, higher fatty acids, higher alcohols, and ester oils. Aqueous raw materials include purified water, alcohol, thickeners, and the like. Examples of powdered raw materials include colored pigments, white pigments, pearlescent agents, and extender pigments. In this embodiment, the cosmetic base raw material can preferably be an oil-based raw material, a powder raw material, or an oil-based raw material and a powder raw material, and more preferably an oil-based raw material.

[0133] The cosmetic material in this embodiment may mean a cosmetic material in which the surface-modified zinc oxide particles are contained in an oil component (oil phase) during the manufacturing process or in the final form, such as an oil-based cosmetic material, an emulsion-type cosmetic material containing surface-modified zinc oxide particles in an oil phase, or a powder solid cosmetic material in which surface-modified zinc oxide particles are mixed with an oil agent and then the oil agent is removed and molded. The emulsion-type cosmetic preparation may be an O / W type emulsion or a W / O type emulsion. In other words, the cosmetic preparation of the present embodiment preferably contains at least one of the surface-modified zinc oxide particles of the present embodiment and the dispersion liquid of the present embodiment in the oil component or oil phase.

[0134] The oil component used in the oil-based cosmetic or oil phase of the emulsion is not particularly limited as long as it is one that is commonly used in cosmetics, such as silicone oil, oils and fats, higher fatty acids, higher alcohols, ester oils, and natural oils.

[0135] Furthermore, the cosmetic preparation of the present embodiment may contain the above-mentioned aqueous raw materials, surfactants, powder raw materials, etc., to the extent that the characteristics of the cosmetic preparation are not impaired.

[0136] The cosmetic material of the present embodiment can be obtained, for example, by blending the surface-modified zinc oxide particles or dispersion of the present embodiment with a cosmetic base such as lotion, cream, sunscreen, foundation, lipstick, blusher, eyeshadow, or the like in a conventional manner.

[0137] In addition, the cosmetic of the present embodiment can be obtained by blending the surface-modified zinc oxide particles of the present embodiment into an oil phase to form an O / W or W / O type emulsion, and then blending the emulsion with the raw materials of the cosmetic.

[0138] The content of the surface-modified zinc oxide particles in the cosmetic of the present embodiment is appropriately adjusted according to the properties of the cosmetic to be produced.For example, the lower limit of the content of the surface-modified zinc oxide particles may be 0.01% by mass or more, 0.1% by mass or more, or 1% by mass or more.The upper limit of the content of the surface-modified zinc oxide particles may be 50% by mass or less, 40% by mass or less, or 30% by mass or less. The upper and lower limits of the content of the surface-modified zinc oxide particles in the cosmetic can be combined in any manner.

[0139] Hereinafter, a sunscreen cosmetic will be specifically described as an example of the cosmetic. In order to effectively block ultraviolet rays, particularly long-wavelength ultraviolet rays (UVA), and obtain a good feeling of use with little powderiness or squeaking, the lower limit of the content of the surface-modified zinc oxide particles in the sunscreen cosmetic is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 1% by mass or more. The upper limit of the content of the surface-modified zinc oxide particles in the sunscreen cosmetic may be 50% by mass or less, 40% by mass or less, or 30% by mass or less. The upper and lower limit values ​​of the content of the surface-modified zinc oxide particles in the sunscreen cosmetic can be arbitrarily combined.

[0140] The sunscreen cosmetic may contain, as necessary, a hydrophobic dispersion medium, inorganic fine particles or inorganic pigments other than the surface-modified zinc oxide particles, a hydrophilic dispersion medium, oils and fats, surfactants, moisturizers, thickeners, pH adjusters, nutrients, antioxidants, fragrances, and the like.

[0141] Examples of hydrophobic dispersion media include hydrocarbon oils such as liquid paraffin, squalane, isoparaffin, branched light paraffin, petrolatum, and ceresin; ester oils such as isopropyl myristate, cetyl isooctanoate, and glyceryl trioctanoate; silicone oils such as decamethylcyclopentasiloxane, dimethylpolysiloxane, and methylphenylpolysiloxane; higher fatty acids such as lauric acid, myristic acid, palmitic acid, and stearic acid; and higher alcohols such as lauryl alcohol, cetyl alcohol, stearyl alcohol, hexyldodecanol, and isostearyl alcohol.

[0142] Examples of inorganic fine particles and inorganic pigments other than the surface-treated particles contained in the cosmetic include calcium carbonate, calcium phosphate (apatite), magnesium carbonate, calcium silicate, magnesium silicate, aluminum silicate, kaolin, talc, titanium oxide, aluminum oxide, yellow iron oxide, γ-iron oxide, cobalt titanate, cobalt violet, and silicon oxide.

[0143] The sunscreen cosmetic may further contain at least one organic ultraviolet absorbing agent.

[0144] Examples of organic ultraviolet absorbers include benzotriazole-based ultraviolet absorbers, benzoylmethane-based ultraviolet absorbers, benzoic acid-based ultraviolet absorbers, anthranilic acid-based ultraviolet absorbers, salicylic acid-based ultraviolet absorbers, cinnamic acid-based ultraviolet absorbers, and silicone-based cinnamic acid ultraviolet absorbers.

[0145] Examples of the benzotriazole-based ultraviolet absorbers include 2,2'-hydroxy-5-methylphenylbenzotriazole, 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole, and 2-(2'-hydroxy-5'-methylphenylbenzotriazole).

[0146] Examples of benzoylmethane ultraviolet absorbers include dibenzalazine, dianisoylmethane, 4-tert-butyl-4'-methoxydibenzoylmethane, 1-(4'-isopropylphenyl)-3-phenylpropane-1,3-dione, and 5-(3,3'-dimethyl-2-norbornylidene)-3-pentan-2-one.

[0147] Examples of benzoic acid-based ultraviolet absorbers include para-aminobenzoic acid (PABA), PABA monoglycerin ester, N,N-dipropoxy PABA ethyl ester, N,N-diethoxy PABA ethyl ester, N,N-dimethyl PABA ethyl ester, N,N-dimethyl PABA butyl ester, and N,N-dimethyl PABA methyl ester.

[0148] Examples of the anthranilic acid-based ultraviolet absorbers include homomenthyl-N-acetylanthranilate.

[0149] Examples of salicylic acid-based ultraviolet absorbers include amyl salicylate, menthyl salicylate, homomenthyl salicylate, octyl salicylate, phenyl salicylate, benzyl salicylate, and p-2-propanol phenyl salicylate.

[0150] Examples of cinnamic acid-based ultraviolet absorbers include octyl methoxycinnamate (ethylhexyl methoxycinnamate), di-paramethoxycinnamate-mono-2-ethylhexanoate glyceryl, octyl cinnamate, ethyl-4-isopropyl cinnamate, methyl-2,5-diisopropyl cinnamate, ethyl-2,4-diisopropyl cinnamate, methyl-2,4-diisopropyl cinnamate, propyl-p-methoxycinnamate, isopropyl-p-methyl cinnamate, and the like. Examples of such cinnamate include 2-ethylhexyl-p-methoxycinnamate, 2-ethoxyethyl-p-methoxycinnamate, cyclohexyl-p-methoxycinnamate, ethyl-α-cyano-β-phenylcinnamate, 2-ethylhexyl-α-cyano-β-phenylcinnamate, and glyceryl mono-2-ethylhexanoyl-di-paramethoxycinnamate.

[0151] Examples of silicone-based cinnamic acid ultraviolet absorbers include [3-bis(trimethylsiloxy)methylsilyl-1-methylpropyl]-3,4,5-trimethoxycinnamate, [3-bis(trimethylsiloxy)methylsilyl-3-methylpropyl]-3,4,5-trimethoxycinnamate, [3-bis(trimethylsiloxy)methylsilylpropyl]-3,4,5-trimethoxycinnamate, [3-bis(trimethylsiloxy)methylsilylbutyl]-3,4,5-trimethoxycinnamate, [3-tris(trimethylsiloxy)silylbutyl]-3,4,5-trimethoxycinnamate, and [3-tris(trimethylsiloxy)silyl-1-methylpropyl]-3,4-dimethoxycinnamate.

[0152] Examples of organic ultraviolet absorbers other than those mentioned above include 3-(4'-methylbenzylidene)-d,l-camphor, 3-benzylidene-d,l-camphor, urocanic acid, urocanic acid ethyl ester, 2-phenyl-5-methylbenzoxazole, 5-(3,3'-dimethyl-2-norbornylidene)-3-pentan-2-one, silicone-modified ultraviolet absorbers, and fluorine-modified ultraviolet absorbers.

[0153] The cosmetic preparation of the present embodiment has excellent ultraviolet shielding properties because it contains the surface-modified zinc oxide particles of the present embodiment. EXAMPLES

[0154] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0155] [Example 1] "Preparation of surface-modified zinc oxide particles" (First step of preparing hydrolyzed liquid) 40.0 g of octyltriethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-3083), 8.0 g of pure water, 0.8 g of 0.1 mol / L hydrochloric acid, and 51.2 g of ethanol were mixed at 60° C. for 90 minutes to obtain a hydrolyzed liquid.

[0156] (Second step of preparing a first mixture) The resulting hydrolysis solution (4 g) and a 36.4 m specific surface area were 2 25 g of zinc oxide particles (manufactured by Sumitomo Osaka Cement Co., Ltd.) having a molecular weight of 1 / g were mixed with 71 g of ethanol. Next, this mixture was dispersed using a bead mill under the following dispersion conditions: rotation speed: 1300 rpm, temperature: 20° C., and dispersion time: 40 minutes. After the dispersion treatment, the beads were removed to obtain a first mixture.

[0157] (Third step of preparing a second mixture) 100 g of the resulting first mixture and 3.0 g of the above hydrolyzed liquid were mixed at 50° C. for 30 minutes to obtain a second mixture.

[0158] (drying process) The resulting second mixture was subjected to solid-liquid separation, dried at 100° C. for 3 hours, and pulverized in a jet mill to obtain the surface-modified zinc oxide particles of Example 1.

[0159] "Measurement of the specific surface area of ​​surface-modified zinc oxide particles" The specific surface area of ​​the surface-modified zinc oxide particles of Example 1 was measured using a fully automatic specific surface area measuring device (product name: Macsorb HM Model-1201, manufactured by Mountec Co., Ltd.) The results are shown in Table 1.

[0160] "Measurement of color difference ΔE of surface-modified zinc oxide particles before and after exposure to simulated sunlight" 3 g of t-butyl methoxydibenzoylmethane, 3 g of polyhydroxystearic acid, and 94 g of tri(caprylic acid / capric acid)glyceryl were mixed together to prepare a solution in which t-butyl methoxydibenzoylmethane was completely dissolved. Next, 2.0 g of the obtained solution and 3.0 g of the surface-modified zinc oxide particles of Example 1 were mixed in a kneader (manufactured by Thinky Corporation, model number: ARE-310) until homogeneous to obtain a mixed solution. Next, the resulting mixture was sandwiched between an assembled quartz cell for a spectrophotometer (manufactured by GL Sciences, model number: AB20-UV-05) so that the optical path length was 0.5 mm, to prepare an assembled cell. Next, the assembled cell obtained was set in an ultraviolet-visible-near infrared spectrophotometer (manufactured by JASCO Corporation, model number: V-770), and the diffuse reflectance spectrum of the mixture was measured using an integrating sphere. From the measurement results, the L1 * , a1 * , b1 * was calculated.

[0161] Next, a xenon lamp from a small light irradiation test device (manufactured by Iwasaki Electric, model number: EYE SUN-CUBE Xenon) was used to measure the cumulative light intensity of 300 kJ / m 2 The assembled cell containing the above mixed solution was irradiated with simulated solar light of 1000 nm. The assembled cell after irradiation was set again in the UV-Vis-NIR spectrophotometer, and the diffuse reflectance spectrum was measured in the same manner. From the measurement results, the L2 * , a2 * , b2 * Calculated. Then, the color difference ΔE = ((L2 * -L1 * ) 2 +(a2 * -a1 * )2 +(b2 * -b1 * ) 2 ) 1 / 2 The results are shown in Table 1.

[0162] "Preparation of dispersion liquid" 10 g of the surface-modified zinc oxide particles of Example 1, 88 g of cyclopentasiloxane (manufactured by Dow Toray, model number: DOWSIL SH245 Fluid), and 2 g of polyglyceryl-3 polydimethylsiloxyethyl dimethicone (manufactured by Shin-Etsu Chemical Co., Ltd., model number: KF-6106) were mixed to obtain a mixed liquid. Next, this mixture was subjected to a dispersion treatment at 9500 rpm for 5 minutes using a homogenizer (manufactured by IKA, ULTRA-TURRAX (registered trademark) series: T25basic) to obtain the dispersion of Example 1.

[0163] "Evaluation of dispersibility based on particle size distribution" A measurement liquid was prepared by diluting the dispersion liquid of Example 1 with cyclopentasiloxane so that the content of the surface-modified zinc oxide particles was 0.1 mass %. Using this measurement solution, a dynamic light scattering particle size distribution analyzer (Microtrack Bell, model number: NANOTRAC WAVE) was used to measure the particle size (d10) when the cumulative volume percentage of the particle size distribution was 10%, the particle size (d50) when the cumulative volume percentage of the particle size distribution was 50%, and the particle size (d90) when the cumulative volume percentage of the particle size distribution was 90%. The results are shown in Table 2.

[0164] "Evaluation of dispersion transparency and UV shielding properties" The dispersion liquid of Example 1 was diluted with cyclopentasiloxane so that the concentration of the surface-modified zinc oxide particles was 0.005% by mass. The diluted solution was placed in a quartz cell with an optical path length of 10 mm, and the total light transmittance (linear transmittance + diffuse transmittance) (%) at 360 nm and the linear transmittance (%) at 550 nm were measured using a UV-Vis-NIR spectrophotometer (manufactured by JASCO Corporation, model number: V-770). The results are shown in Table 2. A low transmittance at 360 nm indicates a high ultraviolet shielding property, and therefore a low transmittance at 360 nm is preferable. A high transmittance at 550 nm indicates high transparency, and therefore, it is preferable that the transmittance at 550 nm is high.

[0165] "Evaluation of temporal stability of surface-modified zinc oxide particles" The surface-modified zinc oxide particles of Example 1 were placed in a porcelain evaporating dish, covered with a polyimide film, and exposed to an environment of 85°C and 95% RH for 48 hours. Using the surface-modified zinc oxide particles of Example 1 after exposure, a dispersion was prepared in the same manner as above. Using the obtained dispersion, the particle size distribution, transparency, and ultraviolet shielding property were measured in the same manner as above. The results are shown in Table 2.

[0166] [Example 2] In the second step of preparing the mixture of Example 1, 2 Instead of using zinc oxide particles with a specific surface area of ​​19.2 m / g, 2 Surface-modified zinc oxide particles of Example 2 were obtained in the same manner as in Example 1, except that zinc oxide particles (manufactured by Sumitomo Osaka Cement Co., Ltd.) of 1.0 g / g were used, 2.4 g of hydrolyzed liquid and 72.6 g of ethanol were used instead of 4 g of hydrolyzed liquid and 71 g of ethanol, and 1.6 g of hydrolyzed liquid was used instead of 3 g of hydrolyzed liquid in the third step of preparing the second mixture of Example 1.

[0167] The specific surface area and color difference ΔE of the surface-modified zinc oxide particles of Example 2 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0168] A dispersion liquid of Example 2 was obtained in the same manner as in Example 1, except that the surface-modified zinc oxide particles of Example 2 were used instead of the surface-modified zinc oxide particles obtained in Example 1. The particle size distribution, transparency and UV shielding property of the dispersion of Example 2 were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0169] The surface-modified zinc oxide particles of Example 2 were exposed to an environment of 85° C. and 95% RH for 48 hours in the same manner as in Example 1. The surface-modified zinc oxide particles of Example 2 after exposure were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0170] [Example 3] In the second step of preparing the mixture of Example 1, 2 Instead of using zinc oxide particles with a specific surface area of ​​4.7 m / g, 2 Surface-modified zinc oxide particles of Example 3 were obtained in the same manner as in Example 1, except that zinc oxide particles (manufactured by Sumitomo Osaka Cement Co., Ltd.) of 1.2 g of hydrolyzed liquid and 73.8 g of ethanol were used instead of using 4 g of hydrolyzed liquid and 71 g of ethanol, and that in the third step of preparing the second mixture of Example 1, 0.8 g of hydrolyzed liquid was used instead of using 3 g of hydrolyzed liquid.

[0171] The specific surface area and color difference ΔE of the surface-modified zinc oxide particles of Example 3 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0172] The dispersion of Example 3 was obtained in the same manner as in Example 1, except that the surface-modified zinc oxide particles of Example 3 were used instead of the surface-modified zinc oxide particles obtained in Example 1. The particle size distribution, transparency and UV shielding property of the dispersion of Example 3 were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0173] The surface-modified zinc oxide particles of Example 3 were exposed to an environment of 85° C. and 95% RH for 48 hours in the same manner as in Example 1. The surface-modified zinc oxide particles of Example 3 after exposure were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0174] [Example 4] (Second step of preparing a first mixture) 7 g of the hydrolyzate obtained in the first step of Example 1 and a granule having a specific surface area of ​​38.7 m 2 25 g of zinc oxide particles (manufactured by Sumitomo Osaka Cement Co., Ltd.) having a molecular weight of 1 / g were mixed with 68 g of ethanol. Next, this mixture was dispersed using a bead mill under the following dispersion conditions: rotation speed: 1300 rpm, temperature: 20° C., and dispersion time: 40 minutes. After the dispersion treatment, the beads were removed to obtain a first mixture.

[0175] (drying process) The obtained first mixture was subjected to solid-liquid separation and dried at 100° C. for 3 hours to obtain surface-modified zinc oxide particles of Example 4.

[0176] The specific surface area and color difference ΔE of the surface-modified zinc oxide particles of Example 4 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0177] The dispersion of Example 4 was obtained in the same manner as in Example 1, except that the surface-modified zinc oxide particles of Example 4 were used instead of the surface-modified zinc oxide particles obtained in Example 1. The particle size distribution, transparency and UV shielding property of the dispersion of Example 4 were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0178] The surface-modified zinc oxide particles of Example 4 were exposed to an environment of 85° C. and 95% RH for 48 hours in the same manner as in Example 1. The surface-modified zinc oxide particles of Example 4 after exposure were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0179] [Example 5] 42 g of the hydrolyzate obtained in the first step of Example 1 and a sieve having a specific surface area of ​​39.4 m 2 The mixture was then charged into a Henschel mixer together with 250 g of zinc oxide particles (manufactured by Sumitomo Osaka Cement Co., Ltd.) having a molecular weight of 1.0 to 1.0 g, and mixed by stirring for 1 hour. The mixture was then dried at 80° C. for 1 hour.

[0180] 250 g of the dried surface-modified zinc oxide particles and 28 g of the hydrolyzed liquid obtained in the first step of Example 1 were charged into a Henschel mixer and mixed by stirring for 1 hour. The resulting mixture was pulverized in a jet mill, and the pulverized powder was dried at 100° C. for 3 hours to obtain surface-modified zinc oxide particles of Example 5.

[0181] The specific surface area and color difference ΔE of the surface-modified zinc oxide particles of Example 5 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0182] The dispersion of Example 5 was obtained in the same manner as in Example 1, except that the surface-modified zinc oxide particles of Example 5 were used instead of the surface-modified zinc oxide particles obtained in Example 1. The particle size distribution, transparency and ultraviolet shielding property of the dispersion of Example 5 were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0183] The surface-modified zinc oxide particles of Example 5 were exposed to an environment of 85° C. and 95% RH for 48 hours in the same manner as in Example 1. The surface-modified zinc oxide particles of Example 5 after exposure were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0184] [Example 6] 69 g of the hydrolyzate obtained in the first step of Example 1 and a granule having a specific surface area of ​​39.4 m 2 The mixture was then charged into a Henschel mixer together with 250 g of zinc oxide particles (manufactured by Sumitomo Osaka Cement Co., Ltd.) having a molecular weight of 1.0 to 1.0 g, and mixed by stirring for 1 hour. The resulting mixture was pulverized in a jet mill, and the pulverized powder was dried at 100° C. for 3 hours to obtain surface-modified zinc oxide particles of Example 6.

[0185] The specific surface area and color difference ΔE of the surface-modified zinc oxide particles of Example 6 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0186] The dispersion of Example 6 was obtained in the same manner as in Example 1, except that the surface-modified zinc oxide particles of Example 6 were used instead of the surface-modified zinc oxide particles obtained in Example 1. The particle size distribution, transparency and UV shielding property of the dispersion of Example 6 were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0187] The surface-modified zinc oxide particles of Example 6 were exposed to an environment of 85° C. and 95% RH for 48 hours in the same manner as in Example 1. The surface-modified zinc oxide particles of Example 6 after exposure were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0188] [Comparative Example 1] Specific surface area is 39.4m 2 100 g of zinc oxide particles (manufactured by Sumitomo Osaka Cement Co., Ltd.) with a molecular weight of 1 / g was placed in a Henschel mixer. While stirring the zinc oxide particles in the Henschel mixer, a mixture of 5 g of octyltriethoxysilane (trade name: KBE-3083, manufactured by Shin-Etsu Chemical Co., Ltd.), 0.375 g of pure water, and 7.125 g of isopropyl alcohol was added. These mixtures were mixed in the Henschel mixer and stirred for 1 hour. The resulting mixture was then pulverized in a jet mill, and the pulverized powder was dried at 100° C. for 3 hours to obtain surface-modified zinc oxide particles of Comparative Example 1.

[0189] The specific surface area and color difference ΔE of the surface-modified zinc oxide particles of Comparative Example 1 were measured in the same manner as in Example 1. The results are shown in Table 1.

[0190] A dispersion liquid of Comparative Example 1 was obtained in the same manner as in Example 1, except that the surface-modified zinc oxide particles of Comparative Example 1 were used instead of the surface-modified zinc oxide particles obtained in Example 1. The particle size distribution, transparency and ultraviolet shielding property of the dispersion of Comparative Example 1 were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0191] The surface-modified zinc oxide particles of Comparative Example 1 were exposed to an environment of 85° C. and 95% RH for 48 hours in the same manner as in Example 1. After exposure, the surface-modified zinc oxide particles of Comparative Example 1 were evaluated in the same manner as in Example 1. The results are shown in Table 2.

[0192] [Comparative Example 2] Specific surface area used in Example 5: 39.4 m 2 / g zinc oxide particles (manufactured by Sumitomo Osaka Cement Co., Ltd.), that is, zinc oxide particles that were not surface-treated, were used as Comparative Example 2, and the color difference ΔE was evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0193] [Table 1]

[0194] [Table 2]

[0195] From the results of Tables 1 and 2, it was confirmed that the surface-modified zinc oxide particles of Examples 1 to 6 have a smaller color difference ΔE and are excellent in ultraviolet shielding properties compared to the surface-modified zinc oxide particles of Comparative Example 1. It was also confirmed that the surface-modified zinc oxide particles surface-treated by a wet method have a smaller d90, are excellent in transparency, and are excellent in ultraviolet shielding properties. It was also confirmed that by performing the mixing step with the hydrolysis liquid twice by a wet method, surface-modified zinc oxide particles having better transparency and ultraviolet shielding properties can be obtained. It was also confirmed by comparing Examples 1 to 3 that by increasing the amount of the surface treatment agent, the deterioration of the surface-modified zinc oxide particles is suppressed even after the accelerated test. [Industrial Applicability]

[0196] The present invention can provide surface-modified zinc oxide particles having excellent ultraviolet shielding properties. The surface-modified zinc oxide particles of the present invention have excellent ultraviolet shielding properties and transparency equal to or greater than that of conventional particles, and therefore have great industrial value when used in cosmetics.

Claims

1. Surface-modified zinc oxide particles, the particle surfaces of which are treated with a hydrolyzable surface treatment agent, the hydrolyzable surface treatment agent is a silane coupling agent having an alkoxy group, The silane coupling agent having an alkoxy group is represented by the following general formula (1): R1Si(OR2)3...(1) (R 1 represents an alkyl group having 1 to 18 carbon atoms, a fluoroalkyl group or a phenyl group, and R 2 represents an alkyl group having 1 to 4 carbon atoms.) Surface-modified zinc oxide particles having a color difference ΔE of 4.0 or less before and after irradiation with simulated solar light.

2. The surface-modified zinc oxide particles described in claim 1, wherein the silane coupling agent having an alkoxy group is at least one selected from the group consisting of n-octyltriethoxysilane, n-octyltrimethoxysilane, and dimethoxydiphenylsilane-triethoxycaprylylsilane crosspolymer.

3. 3. The surface-modified zinc oxide particles according to claim 1, having a total light transmittance of 48% or less at a wavelength of 360 nm.

4. The surface-modified zinc oxide particles according to any one of claims 1 to 3, wherein the surface treatment agent is a hydrolysis product of a silane coupling agent having an alkoxy group.

5. A dispersion comprising the surface-modified zinc oxide particles according to any one of claims 1 to 4 and a dispersion medium.

6. A cosmetic comprising at least one selected from the group consisting of the surface-modified zinc oxide particles according to any one of claims 1 to 4 and the dispersion liquid according to claim 5, and a cosmetic base raw material.

7. A method for producing surface-modified zinc oxide particles according to any one of claims 1 to 4, comprising the steps of: A first step of preparing a hydrolyzed liquid by mixing a surface treatment agent and water; a second step of mixing the hydrolyzed liquid with zinc oxide particles to prepare a first mixture; and drying the first mixture obtained in the second step.

Citation Information

Patent Citations

  • Ultraviolet ray-blocking composite fine particle, its production and cosmetic

    JP1997100112A

  • Silica-coated zinc oxide particle, its preparation, and composition containing it

    JP1999193354A

  • Zinc oxide powder and its synthesis

    JP2000095519A

  • Method for producing fine powder of zinc oxide, fine powder of zinc oxide and resin composition containing it

    JP2002284527A

  • Low smell alkylsilylated powder, method for producing the same, silicone oil slurry dispersed with the low smell alkylsilylated powder, and cosmetic mixed with the low smell alkylsilylated powder or the silicone oil slurry

    JP2007051188A